Study of Cassava Peel Biomass and Spent Bleaching Earth (SBE) as Raw Material for Refused Derived Fuel (RDF) - Hudayarizka, Riza; Anifah, Eka Masrifatus; Sholikah, Umi; Ariani, Ismi Khairunnissa; Wijaya, Siti Iniz Khairunisa (JPSE (Journal of Physical Science and Engineering), 2024)
Cassava, a widely used raw material in Indonesia's food industry, amounted to 14.9 million tons in 2022. Typically, cassava peel, comprising 2-5% of the plant, is discarded in landfills or left untreated. However, recent research suggests its potential as a source of refuse-derived fuel (RDF), given its high calorific value of 4253 kcal/kg and 12.55% fixed carbon. Another potential RDF source is spent bleaching earth (SBE), a by-product of oil treatment, containing 20-40% oil. This study explores the impact of different compositions of cassava peel, SBE, and various binders on RDF characteristics. Binders like tapioca flour, durian seed, and rejected papaya were tested in ratios ranging from 70:20:10 to 90:0:10. The findings reveal that the 90:0:10 composition with rejected papaya binder yielded RDF with the highest calorific value and volatile matter content. Specifically, RDF from 90% cassava peel exhibited a calorific value of 5320 kcal/kg, fixed carbon of 13.9%, volatile matter of 80%, ash content of 5.7%, and moisture content of 0.3%. These results meet Indonesia's RDF standards, which mandate a calorific value above 3000 kcal/kg and volatile matter between 50-80%.